360 Health Analysis (H360) – Quality of Life of Breast Cancer Patients: an Integrated Vision - Semedo, Patrícia Miguel; Coelho, Sara; Rêgo, Inês Brandão; Cavaco-Silva, Joana; Teixeira, Laetitia; Sousa, Susana; Pavão, Francisco; Leite, Ricardo Baptista; Costa, Luís (Archives of Clinical and Biomedical Research, 2023)
Background: This study is part of the H360 Health Analysis (H360) and aimed to investigate the Quality of Life (QoL) of Breast Cancer (BC) patients in the real world. Methods: Two questionnaires (EORTC QLQ?C30 version 3.0 and its breast-specific module QLQ?BR23) validated for the Portuguese population were applied to assess BC patients’ QoL in seven Portuguese hospitals. Results: BC was diagnosed in early stage in 68%, in locally advanced stage in 5%, and in advanced stage in 22% of patients. Patients’ median age was 59 years (range 35-85). Most (97%) received surgery for the primary tumor, 27% radiotherapy, 24% chemotherapy, 15% endocrine therapy, and 6% targeted therapy. Women who completed the survey reported a mean overall health rate of 4.9 and a mean QoL rate of 5 on a 7-point Likert-type scale. Some degree of impairment in strenuous activities or taking long walks was reported by 84% and 64% of women, respectively. Negative psychological impact was reported by 71%. Pain was the most frequent symptom (57%), interfering with daily activities for 46% of women. Work and daily activities were impaired in 56%, social activities in 23%, and family activities in 26% of BC patients, with 34% reporting financial difficulties. Conclusions: Adequate support and strategies are required to address the clinical, physical, and psychosocial needs of BC survivors. This study reinforces the need to refer these patients to appropriate interventions (as psycho-oncological and social support), develop a framework for work alternatives, and promote a more active lifestyle.